Temporal heat stress mitigation and physiological response in Abelmoschus esculentus L. by foliarly supplied salicylic acid - Usama Bin Khalid; Shah, Basharat Hussain; Ahmed, ,Imtiaz; Ali, Mujahid; Ayyub, Saqib; Ahmad, Muhammad (Journal of Pure and Applied Agriculture, 2023)
Elevated global temperatures due to climate change have emerged as a significant concern for vegetable production. Heat stress drastically affects various physiological, developmental, and growth processes in horticultural crops. The temperature was enhanced gradually when the early sown plant was 50 days old (S1), the second sown plant was 40 days old (S2), and the third sown plant was 30 days old (S3). Foliar applications of salicylic acid (1.5 mM) on the vegetative and physiological response of open-pollinated okra cultivar ‘Sabzpari’ plants subjected to heat-induced stress. The findings indicated that all sowing intervals significantly influenced plant vegetative and physiological attributes compared to control. Furthermore, S1 plants exhibit more resilience to heat stress in comparison to S2 and S3 plants. In addition, the S1 plant with foliar supplied 1.5 mM salicylic acid, exhibited a higher number of leaves, shoot length, root length, fresh weight, dry weight, chlorophyll contents, photosynthetic rate, stomatal conductance, water use efficiency, and lower transpiration rate under heat stress conditions. By applying SA, the dry biomass of the seedling increased 1.30 times as compared to the control. In S1, dry biomass increased 1.33 times as compared to control. Notably, the treatment of 1.5 mM SA led to a significant increase of approximately 1.19 times as compared to the control, and among sowing intervals, S1 showed 1.19 times increase. Nevertheless, the okra plants exhibited significant resilience to heat stress when salicylic acid was applied during the S1 interval. Hence, the application of salicylic acid (1.5 mM) through foliar spraying, specifically at the S1 interval, presents a practical strategy for mitigating the detrimental impacts of heat stress on the okra cultivar ‘Sabzpari’.